2014
DOI: 10.1177/1087054714542002
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Characteristics and ADHD

Abstract: Neighborhood social support is a potential area of intervention for children with ADHD and their caregivers. Research challenges and opportunities are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Other research that reported findings of salutary impacts on health and well-being confirmed that both perceptions of social support and actual social support had beneficial health impacts [18,45,63,67,82,104,110,151,152,154,155,156,157,158,159,160,161,162,163]. Similarly, research offered evidence that low quality social relations, lacking social support, or high social disadvantage have adverse health impacts including, but not limited to, general mental/physical health problems, attention deficit hyperactivity disorder (ADHD), obesity, and cardiometabolic disease [17,64,107,164,165,166]. Five studies (17%) had either inconclusive or non-significant results for social support impacts on health and well-being [90,92,108,162,167].…”
Section: Resultsmentioning
confidence: 99%
“…Other research that reported findings of salutary impacts on health and well-being confirmed that both perceptions of social support and actual social support had beneficial health impacts [18,45,63,67,82,104,110,151,152,154,155,156,157,158,159,160,161,162,163]. Similarly, research offered evidence that low quality social relations, lacking social support, or high social disadvantage have adverse health impacts including, but not limited to, general mental/physical health problems, attention deficit hyperactivity disorder (ADHD), obesity, and cardiometabolic disease [17,64,107,164,165,166]. Five studies (17%) had either inconclusive or non-significant results for social support impacts on health and well-being [90,92,108,162,167].…”
Section: Resultsmentioning
confidence: 99%
“…While the literature has discussed links between the residential stability of the child and these disorders, there has been little discussion about the role that resident churn might play in delaying such diagnoses. Perhaps this reflects a decrease in connections to neighborhood information networks, weakened norms and social ties to neighbors-connections which might facilitate knowledge about and help-seeking for such disorders, as well as provide social support to affected children and their families [15].…”
Section: Neighborhood Instabilitymentioning
confidence: 99%
“…Neighborhoods may affect children's development through a variety of causal mechanisms operating either through social, institutional or biological processes; for extended discussions see Sampson, Morenoff and Gannon-Rowley [12] and Galster [11]. The potential neighborhood social mechanisms relevant for neurodevelopmental outcomes include: neighborhood deprivation [13,14]; social cohesion and control [15]; ethnic mix [16]; violence and social disorder [17]; institutional resources [18]; physical surroundings [19,20]; and exposure to environmental pollutants [6,9,[21][22][23]. These mechanisms may affect health outcomes via biological responses and/or alterations in health and risk behaviors and usage of health facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published literature suggests a litany of risk factors associated with the etiology of ADHD, ranging from physical and social environmental factors (Perera et al, 2014;Razani et al, 2014) to genetic (Laucht, Hohm, Esser, Schmidt, & Becker, 2007) and dietary factors (Howard et al, 2011). The relationship between sleep and ADHD is of increasing research interest, however certain aspects of this association remain understudied.…”
mentioning
confidence: 99%